Correlation between the Size of Tumour with Early Postoperative Serum Sodium Imbalance in Sellar and Suprasellar Space Occupying Lesion after Transsphenoidal surgery - Hossain, Muhammad Mahabub; Kadir, Md Lylatul; Jahan, Naznin Akter; Hasan, Md Motasimul; Uddin, Kazi Hafiz; Saha, Milton Kumer; Hafiz, Ahsan Mohammed; Barua, Kanak Kanti (Bangladesh Journal of Neurosurgery, 2020)
Background: Seller and suprasellar space occupying lesions are frequently encountered intracranial lesions now-a-days. Surgery through transsphenoidal route is the most preferable approach which is frequently performed for excision of these space occupying lesions. The lesions are located in a very critical area because they are surrounded by the hypothalamus, pituitary gland and cavernous sinus which are responsible to maintain various hormonal functions as well as regulation of plasma osmolality and plasma electrolytes. So, during and after operation various types of osmolality and electrolytes related complications are often encountered. Among them serum sodium imbalance is the most frequent one. Objective: Tumour size is one of the very important predisposing factors which influence the serum sodium level after surgery. For investigating the correlation between the size of sellar and suprasellar space occupying lesions with the incidence of postoperative sodium imbalance after transsphenoidal surgery of the patient having these lesions. Material and method: Thirty patients with sellar and suprasellar space occupying lesions meeting the inclusion criteria were enrolled. The largest diameter of the tumour was measured in the coronal or sagittal planes from pre-operative MRI’s. They underwent transsphenoidal surgery and were observed for first 7 postoperative days and serum electrolytes was measured every day. Patients in this study were considered to have serum sodium imbalance if the narrow range of 135-145 mmol/L was not maintained. Then according to the tumour size they were divided in to two groups. Then the two groups were compared and the frequency of development of post-operative sodium imbalance, their time of onset and types of imbalances were observed. Result: 60% of the patients in our study developed post operative serum sodium imbalance after transsphenoidal surgery. Among them 40% of the patients developed hypernatraemia, 13.3% of the patient developed hyponatraemia and only 6.7% patient developed combined imbalance. Hypernatraemia is more common than hyponatraemia after transsphenoidal surgery. Peak incidence of hyponatraemia occurred on 3rd post-operative day and hypernatraemia occurred at 1st postoperative day. In the large size tumour group (>30mm) 46.66% had serum sodium imbalance and imbalance was observed in 13.33% of the small size group (d”30mm) and there is significant difference of sodium imbalance between large and small size group and p-value was 0.001. r- value 0.776 indicates that the size of the tumour strongly correlates with postoperative sodium imbalance and there is significant association between size of the tumour with sodium imbalance. The study found no significant association between age, sex or types of the lesions with postoperative sodium imbalance (p=0.43). Conclusion: Post operative serum sodium imbalance after transsphenoidal surgery is a burning issue for the neurosurgeon now a day. Early prediction of these types of notorious complication is helpful for preoperative and post operative management of the patient. The size of the lesion is one of the most significant markers. As well as a strong association between size of the tumour with post operative sodium imbalance was found. This will help us in perioperative management of the patients, and reduces complication related mortality and morbidity after the transsphenoidal surgery. Bang. J Neurosurgery 2020; 10(1): 82-91